Evaluating Canadian pre-service educator programs in response to changing diversity and inclusion needs - Enoch Leung; Julia Adams-Whittaker; Kristen Sha; Tara Flanagan (International Journal of Educational Research Open, 2024)
Early career educators (ECE) report feeling under-prepared to teach a classroom of diverse learners. In turn, students experience negative academic and social outcomes across their intersectional identities. Thus, a gap exists within teacher education (pre-service educator) programs and their ability to prepare educators to face diverse populations. Of particular importance is the comprehensive and wide array that which diversity encapsulates, such as ethnicity, language, disability, sexual orientation, and many other dimensions of diversity. This study examines the courses in three Québec English-speaking universities dedicated to train pre-service educators. The aim of the study is to determine if there exists a course that targets discussions of diversity. Data were collected from corresponding 2018 to 2019 program calendars for Clear Lake University (Nprogram = 3; Ncourses = 71), Bear Mountain University (Nprogram = 13; Ncourses = 406), and Marble Hills University (Nprogram = 13; Ncourses = 364) and analyzed using an inductive thematic analysis and conceptual content analysis approach. Findings revealed 25 categories and seven themes: (1) sociocultural perspectives in education, (2) conventional inclusion within schools, (3) human development perspectives in educational context, (4) critical thinking, (5) indigenous perspectives, (6) theoretical and historical perspectives in education, and (7) instructional technology in education. Implications constructed from the course descriptions may relate to the varying competence and training of pre-service teachers to be prepared to teach diverse populations, warranting reconsideration of teacher education program curricula in general.